Ремісниче населення Житомира (за матеріалами ревізького перепису 1833 року) - Мартинчук, Світлана; Martynchuk, Svitlana (Східноєвропейський національний університет ім. Лесі Українки, 2013)
На підставі аналізу ревізької «сказки» 1833 р. схарактеризовано основні соціальні стани, на які поділялися мешканці центру Волинської губернії. Установлено, що в складі населення Житомира переважали міщани, цехові ремісники й купці. Матеріали перепису послугували основою для виявлення і порівняння вікової та статевої структури цехових ремісників.According to the analysis census «tales» in 1833 basic social conditions into which the residents of the center of Volyn province were divided, are characterized. It was established that tradesmen, artisans and merchants prevailed in the population of Zhitomir. In 1833, there were 8 workshops, bringing together 11 artisan specialties. Among the guild population tailors, shoemakers, bakers, ceareals makers, coper makers, silver makers prevailed. The most numerous was tailors shop - which engaged people in deep making; the smallest shop was the barbers who providing surgical care, and lealing wounds.
Keywords: Волинська губернія; Житомир; ремісники; ремісничий цех; віково-статева структура населення; Volyn province; Zhitomir; artisans; craft shop; age-sex structure of the population